Implementation of Group Counseling with The Gestalt Approach - Fauzi Isra Fauzi; Yeni Karneli; Netrawati Netrawati (Bisma The Journal of Counseling, 2020)
Every human being must have problems, whether those problems as the implications in addressing a less conductive environment and person environment who could not afford to be organized so that resulted in the birth of the abnormal behaviors. Gestalt counseling approach wanted improve individuals by focusing on the present perspective, through the projection of the past phenomenon with the present condition. In gestalt group counseling, group member can make use of their presence in the group to channel and express their thoughts, feelings and behavior so far that is problematic. To be able to achieve effective and efficient group activities, a gestalt group leader must be able to carry out activities according to the stages of forming group counseling.